Comparative studies of the amino acid and nucleotide sequences of pilin derived from Pseudomonas aeruginosa PAK and PAO. - Sastry, P A (1985)
The entire amino acid sequence for Pseudomonas aeruginosa PAO pilin was determined through peptide sequencing and from the complete nucleotide sequence encoding the pilin gene. The precursor PAO pilin is 149 amino acids in length which includes a 6-amino-acid positively charged leader sequence. Comparison of the amino acid sequences of pilin produced by P. aeruginosa PAO and PAK reveals a region of high homology corresponding to the leader peptide and residues 1 to 54 of the mature pilin. The amino acid sequence of the peptide encompassing the major antigenic determinant of PAK differs greatly from that of the equivalent region in PAO. The C-terminal regions of these proteins are semiconserved. Few major differences were found when the predicted secondary structures for PAO and PAK pilins were compared. Major nucleotide sequence variation between the equivalent restriction fragments from PAO and PAK occurred within the areas coding for the peptides containing the immunodominant site for PAK pilin and the C termini.